Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1103/physrevlett.116.016802
|View full text |Cite
|
Sign up to set email alerts
|

Floquet-Engineered Valleytronics in Dirac Systems

Abstract: Valley degrees of freedom offer a potential resource for quantum information processing if they can be effectively controlled. We discuss an optical approach to this problem in which intense light breaks electronic symmetries of a two-dimensional Dirac material. The resulting quasienergy structures may then differ for different valleys, so that the Floquet physics of the system can be exploited to produce highly polarized valley currents. This physics can be utilized to realize a valley valve whose behavior is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 38 publications
(57 reference statements)
0
59
0
Order By: Relevance
“…In the last few years, the concept of engineering such periodically driven systems, often called Floquet systems, has gained prominence, particularly due to the feasibility of experiments in solid state 6 as well as in photonic 7 and cold atom systems 8 . Floquet topological systems have been studied extensively to predict non-equilibrium Majorana modes [9][10][11] , non-trivial transport properties [12][13][14][15] as well as to control the band-structure 3,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the concept of engineering such periodically driven systems, often called Floquet systems, has gained prominence, particularly due to the feasibility of experiments in solid state 6 as well as in photonic 7 and cold atom systems 8 . Floquet topological systems have been studied extensively to predict non-equilibrium Majorana modes [9][10][11] , non-trivial transport properties [12][13][14][15] as well as to control the band-structure 3,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…This two-dimensional (2D) material has been grown experimentally by successful deposition of silicene sheet on silver substrate [9][10][11] . Also the interest in silicene soared due to the possibility of its various future applications ranging from spintronics [13][14][15][16][17] , valleytronics [18][19][20][21][22] to silicon based transistor 23 at room temperature. Very recently, it has been reported that low energy excitations in silicene follows relativistic Dirac equation akin to graphene 7,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Our finding reveals more general valley selection rules and promises enhanced control over the valleytronic properties of Dirac materials, such as graphene, TMDs, as well as Weyl semimetals. Furthermore, by using higher pump intensity or lower pump photon energy with selective light helicity, we expect to reveal higher-order coherent effects that could produce polarized valley current in transport experiments [114].…”
Section: Discussionmentioning
confidence: 99%